2019
DOI: 10.1038/s41598-018-36415-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic fingerprint of coronary blood in STEMI patients depends on the ischemic time and inflammatory state

Abstract: In this study we investigated whether the metabolomic analysis could identify a specific fingerprint of coronary blood collected during primary PCI in STEMI patients. Fifteen samples was subjected to metabolomic analysis. Subsequently, the study population was divided into two groups according to the peripheral blood neutrophil-to-lymphocyte ratio (NLR), a marker of the systemic inflammatory response. Regression analysis was then applied separately to the two NLR groups. A partial least square (PLS) regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A handful of metabolomic studies have been conducted in patients presenting with STEMI 2325 . But none of these studies have investigated the time-effect changes in plasma metabolome before and after PPCI which is crucial to provide insights into the altered metabolic pathways with clinical relevance during I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of metabolomic studies have been conducted in patients presenting with STEMI 2325 . But none of these studies have investigated the time-effect changes in plasma metabolome before and after PPCI which is crucial to provide insights into the altered metabolic pathways with clinical relevance during I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…An early metabolomics study showed that 1H-NMR spectroscopy could correctly diagnose the presence of CAD and assess its severity [40]. Other applications of NMR-based metabolic profiling in ACS mainly include analysis of both urine [36] and serum [33,34] metabolites for unstable angina pectoris disease, investigating the serum metabolic characteristics of acute myocardial infarction (AMI) patients in comparison with those of chest pain controls [41], and deciphering the metabolomic fingerprint of coronary blood in STEMI patients [42]. Abbreviations: STEMI, ST-elevation myocardial infarction; NSTEMI, non-ST-elevation myocardial infarction; NSTEACS, non-ST-elevation ACS; NOCAD, nonobstructive coronary artery disease; AMI, acute myocardial infarction; AHF, acute heart failure; MI, myocardial infarction; SA, stable angina pectoris; UA, unstable angina pectoris; PCI, percutaneous coronary intervention; ACS, acute coronary syndromes; CAD, coronary artery disease; HC, healthy control; LC/MS, liquid chromatography/mass spectrometry; GC/MS, gas chromatography/mass spectrometry; H-NMR, proton nuclear magnetic resonance; SPME, solid-phase microextraction; LPC, lysophosphatidylcholine; LPE, lysophosphatidylethanolamine; TCA, tricarboxylic acid cycle.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Metabolomics is a powerful analytical tool used for the identification of low molecular weight molecules, able to capture disease-specific metabolic signatures as possible biomarkers. In the last 10 years, metabolomics has been applied widely and successfully in various fields of medicine for the study and discrimination of various pathologies such as cardiovascular 29,30 and neurodegenerative and psychiatric diseases 31,32 , as well as cancer 33 . To date, the pathogenesis of FM and specifically of IEI-EMF is completely unknown.…”
mentioning
confidence: 99%